Economic evaluation of different strategy for weed management in garlic production - Štefanić, Edita (Array, 2020)
A field experiment was conducted to evaluate various weed management options on garlic (Alium sativum L.) production in Northeastern Croatia. This study focus on how different strategies of weed control affects weed community composition and economic benefit of weed management. An experiment was arranged as a complete block design with three different weed management strategies: chemical control (PRE EM and POST EM), mechanical control (three times during the season), and combination of chemical and mechanical treatments, together with weeded checks. Data on weed density, fresh above weed biomass and garlic yield per m2 were collected at the end of the growing season, and were subjected to statistical and economic analysis. The mayor weeds found in the experimental plots were: Sorghum halepense, Ambrosia artemisiifolia, Cirsium arvense and Chenopodium album. The various weed growth (density and biomass) and yield varied with application of weed management practices. Significantly lower values of weed density and fresh above weed biomass were recorded on plots with mechanical and combination of chemical and mechanical treatments compared to weeded check. Chemical application gave in this study insufficient weed control and resulted in lower yields compared to the mechanical treatments and combination of mechanical and mechanical weed control. The best cost: benefit ratio was observed on treatment with combination of chemical and mechanical weed control and can be successfully applied to boost up the bulb yield in garlic and to harvest the maximum profit for farmers.